2009
DOI: 10.1080/13550280902725550
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus meningitis with hypoglycorrhachia in the absence of rash in an immunocompetent woman

Abstract: We report varicella-zoster virus (VZV) meningitis in a healthy adult woman with no antecedent rash and with hypoglycorrhachia. Cerebrospinal fluid (CSF) examination revealed the presence of VZV DNA, anti-VZV immunoglobulin G (IgG) antibody, and intrathecal production of anti-VZV IgG antibody.Keywords varicella zoster; meningitis; hypoglycorrhachia; PCR; immunocompetent Case reportA 26-year-old healthy Bhutanese woman developed increasing throbbing bitemporal headache with photophobia, severe nausea, and vomiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
(30 reference statements)
2
28
0
Order By: Relevance
“…Habib et al 6 reported herpes zoster meningitis with hypoglycorrhachia in an immunocompetent patient, similar to our case, except that in our case the patient had late-onset zoster rash. Primary infection of VZV causes varicella (chickenpox), after which the virus can remain latent in a cranial nerve or dorsal root ganglia at any point of the neural axis.…”
Section: Discussionsupporting
confidence: 87%
“…Habib et al 6 reported herpes zoster meningitis with hypoglycorrhachia in an immunocompetent patient, similar to our case, except that in our case the patient had late-onset zoster rash. Primary infection of VZV causes varicella (chickenpox), after which the virus can remain latent in a cranial nerve or dorsal root ganglia at any point of the neural axis.…”
Section: Discussionsupporting
confidence: 87%
“…Neither neck stiffness nor skin rashes were observed in our patient. The absence of neck stiffness is not uncommon in patients with VZV meningitis, whereas the onset of VZV infection without an apparent skin rash is unusual, although cases of VZV meningitis without rashes have been reported (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Like VZV vasculopathy, they also occur in the absence of zoster rash, as demonstrated by reports of VZV meningitis [9], meningoradiculitis [10], and cerebellitis [11], in which diagnosis was confirmed by the detection of VZV DNA or anti-VZV antibody or both in CSF.…”
Section: Neurological Complications Of Vzv Reactivationmentioning
confidence: 98%